Destruction of cultural heritage in 19th-century France : old stones versus modern identities - Greenhalgh, Michael (Heritage and identity (Series) ;, 2015)
Destruction of Cultural Heritage in 19th Century France charts the destruction of earlier architecture as towns pull down their walls, build modern houses, welcome railways and, except for a few scholars, forget about the past. Heritage was largely scorned, and identity found in modernity, not in the past.